Anode-free lithium secondary battery having dual-coated anode current collector

KR1020260153172APending Publication Date: 2026-10-21BEILAB CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020260071076
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2026-04-20
Publication Date
2026-10-21

Smart Images

  • Figure PAT00006_ABST
    Figure PAT00006_ABST
Patent Text Reader

Abstract

The present invention relates to a non-anode lithium secondary battery having a negative electrode current collector having a dual coating layer formed thereon, wherein a positive active material, a separator, and an electrolyte are provided between a positive electrode current collector and a negative electrode current collector, wherein an artificial SEI layer of metal is coated on the negative electrode current collector, and a naturally occurring SEI film is formed on the negative electrode current collector by a reaction between at least a portion of the artificial SEI layer and the electrolyte during the initial charging of the non-anode lithium secondary battery. According to the present invention, a non-anode lithium secondary battery can be provided that can suppress the occurrence of dendrites on a negative electrode current collector and improve the capacity and lifespan of the battery by means of a dual coating layer comprising artificial SEI and naturally formed SEI that is pre-coated on a negative electrode current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a non-anode lithium secondary battery, and specifically, to a non-anode lithium secondary battery that can suppress the occurrence of dendrites on a negative electrode current collector and improve the capacity and lifespan of the battery by forming a dual coating layer on a negative electrode current collector. Background Technology

[0002] A lithium secondary battery is manufactured by using materials capable of inserting and extracting lithium ions as the negative and positive electrodes, and by filling an organic electrolyte or a polymer electrolyte between the positive and negative electrodes, and generates electrical energy through oxidation and reduction reactions when lithium ions are inserted and extracted from the positive and negative electrodes.

[0003] The lithium film (lithium layer) commonly used in lithium-ion batteries is not only prone to oxidation but can also melt at relatively low temperatures, making manufacturing and performance maintenance difficult and posing a problem of increasing product unit costs due to its high price.

[0004] In lithium secondary batteries, the implementation of a cathode-free technology that does not use a lithium film (lithium layer) in the negative electrode can solve the aforementioned safety issues and drastically reduce process costs.

[0005] However, the cathode-free technology of lithium-ion batteries has a problem in that dendrites form on the negative electrode current collector during the battery charging process. These dendrites cause the battery to expand, leading to instability at the electrode-electrolyte interface during the battery cycle and potentially shortening the battery's lifespan. Furthermore, these dendrites can penetrate the separator, causing an internal short circuit in the battery, which can trigger thermal runaway and lead to combustion explosions. Prior art literature

[0006] Republic of Korea Registered Patent No. 10-2115596 The problem to be solved

[0007] The present invention aims to solve the aforementioned problems by providing a non-anode lithium secondary battery that can suppress the occurrence of dendrites and improve the capacity and lifespan of the battery through a dual coating layer comprising an artificial solid electrolyte interphase (SEI) that is pre-coated on a negative electrode current collector and a natural solid electrolyte interphase (SEI) that is formed on the negative electrode current collector during the initial charging of the battery. means of solving the problem

[0008] The present invention, for achieving the aforementioned objectives, can provide a non-anode lithium secondary battery having a negative electrode current collector having a dual coating layer formed thereon, wherein a positive active material, a separator, and an electrolyte are provided between a positive electrode current collector and a negative electrode current collector, wherein an artificial SEI layer of metal is coated on the negative electrode current collector, and during the initial charging of the non-anode lithium secondary battery, a naturally occurring SEI film is formed on the negative electrode current collector by a reaction between at least a portion of the artificial SEI layer and the electrolyte.

[0009] During the initial charging of the above-mentioned non-cathode lithium secondary battery, the naturally occurring SEI film may be formed on the negative current collector by the reaction between the entire artificial SEI layer and the electrolyte.

[0010] During the initial charging of the above-mentioned anode-free lithium secondary battery, the naturally occurring SEI film may be formed on the artificial SEI layer that remains unreacted due to the reaction between a portion of the artificial SEI layer and the electrolyte.

[0011] The artificial SEI layer can be coated on the cathode current collector in advance before the cathode current collector comes into contact with the electrolyte.

[0012] The above electrolyte is a local high-concentration electrolyte or a fluorinated electrolyte, and the artificial SEI layer may comprise a mixture of metals selected from the group consisting of transition metals.

[0013] The above artificial SEI layer can be formed as an Ag-Ti system.

[0014] In the Ag-Ti system of the artificial SEI layer, the volume of Ag may be larger than the volume of Ti.

[0015] For example, the Ag-Ti system of the artificial SEI layer may contain 5 to 25% of the volume of Ti based on the total volume of the Ag-Ti system.

[0016] Preferably, the Ag-Ti system of the artificial SEI layer may contain Ag:Ti in a volume ratio of 4:1 to 16:1 based on the total volume of the Ag-Ti system.

[0017] More preferably, the Ag-Ti system of the artificial SEI layer may contain Ag:Ti in a volume ratio of 10:1 based on the total volume of the Ag-Ti system.

[0018] For example, when the cathode current collector coated with the artificial SEI layer is tested by copper K-alpha rays, the Ag-Ti system can be formed such that a characteristic peak appears at at least one of 2θ=38°, 2θ=44°, 2θ=64° and 2θ=77° of the X-ray diffraction pattern.

[0019] Preferably, when the cathode current collector coated with the artificial SEI layer is tested by copper K-alpha rays, the Ag-Ti system can be formed such that characteristic peaks appear at 2θ=38°, 2θ=44°, 2θ=64°, and 2θ=77° of the X-ray diffraction pattern. Effects of the invention

[0020] According to the present invention, a non-anode lithium secondary battery can be provided that can suppress the occurrence of dendrites on a negative electrode current collector and improve the capacity and lifespan of the battery by means of a dual coating layer comprising artificial SEI and naturally formed SEI that is pre-coated on a negative electrode current collector. Brief explanation of the drawing

[0021] FIG. 1 is a conceptual diagram showing a non-cathode lithium secondary battery having a negative electrode current collector coated with an artificial SEI layer according to an embodiment of the present invention. Figure 2 is a conceptual diagram showing a non-cathode lithium secondary battery having a negative electrode current collector without an artificial SEI layer as a comparative example. Figure 3a is a microscopic image of the surface of a negative current collector coated with an artificial SEI layer, and Figure 3b is a microscopic image of the surface of a negative current collector without an artificial SEI layer as a comparative example. Figure 4a is a microscopic image of a cross-section of the cathode layer on a cathode current collector coated with an artificial SEI layer, and Figure 4b is a microscopic image of a cross-section of the cathode layer on a cathode current collector without an artificial SEI layer as a comparative example. Figure 5 is a diagram showing a comparison of capacity retention rates according to the number of charge and discharge cycles in the case where an artificial SEI layer is applied and in the case where it is not applied. Figure 6 is a diagram showing a comparison of capacity retention rates according to the number of charge and discharge cycles. Figure 7 is a diagram showing a comparison of the number of charge and discharge cycles of a battery until the State of Health (SOH) reaches 80%. Figure 8 is a diagram showing the results of testing a cathode current collector coated with an artificial SEI layer by copper K-alpha line. Specific details for implementing the invention

[0022] Hereinafter, a lithium secondary battery according to an embodiment of the present invention will be described in detail with reference to the attached drawings. The attached drawings illustrate exemplary forms of the present invention and are provided merely to explain the present invention in more detail; the technical scope of the present invention is not limited thereby.

[0023] Additionally, identical or corresponding components are assigned the same reference number regardless of the drawing symbol, and redundant descriptions thereof are omitted; furthermore, for the convenience of explanation, the size and shape of each illustrated component may be exaggerated or reduced.

[0024] In addition, in describing the present invention, detailed descriptions of related prior art are omitted if it is determined that such descriptions could obscure the essence of the invention.

[0026] FIG. 1 is a conceptual diagram showing a negative electrode lithium secondary battery having a negative electrode current collector coated with an artificial SEI layer according to an embodiment of the present invention, and FIG. 2 is a conceptual diagram showing a negative electrode lithium secondary battery having a negative electrode current collector without an artificial SEI layer as a comparative example.

[0027] In FIGS. 1 and 2, the illustration of the cathode layer is omitted to more clearly distinguish between the artificial SEI layer (70) and the naturally occurring SEI film (80) formed on the cathode current collector (10) to be described later.

[0028] For example, during charging, lithium ions separated from the positive electrode active material move toward the negative electrode current collector and are reduced on the negative electrode current collector to form a negative electrode layer (i.e., a lithium layer). Additionally, during discharging, the negative electrode layer is oxidized to generate lithium ions, and the generated lithium ions can be reduced in the positive electrode active material.

[0029] In the present invention, the negative electrode active material and the negative electrode plate are not provided separately. That is, the present invention relates to a negative electrode-free lithium secondary battery.

[0030] Referring to FIGS. 1 and 2, a non-negative lithium secondary battery may include a negative electrode current collector (10), a positive electrode current collector (20), a positive electrode active material (30), an electrolyte (40), and a separator (50). For example, a liquid electrolyte (40) may be provided between the positive electrode current collector (20) and the negative electrode current collector (10).

[0031] The material of the above negative electrode current collector (10) can be used without special restrictions as long as it is a material having high conductivity without causing chemical changes in the lithium secondary battery. For example, the material of the negative electrode current collector (10) may be copper, iron, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. Preferably, the negative electrode current collector (10) may be formed of copper or stainless steel.

[0032] The above positive current collector (20) may be formed of aluminum, an aluminum polymer composite, etc. A separator (50) and a positive active material (30) may be disposed between the above negative current collector (10) and the above positive current collector (20).

[0033] The separator (50) is disposed between the negative current collector (10) and the positive plate formed by the positive active material (30), thereby separating the negative current collector (10) and the positive active material (30) (or positive plate) from each other. Additionally, the separator (50) can provide a passage for the movement of lithium ions and can be used without special limitations as long as it is typically used as a separator in a lithium secondary battery.

[0034] For example, it is desirable that the separator (50) has low resistance to the movement of ions through the electrolyte. For example, the separator (50) may be formed from at least one of polyethylene, polypropylene, or a copolymer of polyethylene and polypropylene, and it is also possible to form a multilayer film of two or more layers thereof.

[0035] The above electrolyte may be a liquid electrolyte. The above liquid electrolyte may be a non-aqueous electrolyte solution. The non-aqueous electrolyte solution may comprise an electrolyte which is a lithium salt and a medium which is a solvent.

[0036] The above lithium salts are lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(pentafluoroethanesulfonyl)imide (LiBETI), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate Lithium salt (LiBOB, Lithium bis(oxalato)borate), Lithium oxalyldifluoroborate salt (LiODFB, Lithium oxalyldifluoroborate), Lithium trifluoromethanesulfonylimide salt (LiTSFI, Lithium trifluoromethanesulfonylimide), Lithium fluorosulfamoylimide salt (LiFSAM, Lithium fluorosulfamoylimide), Lithium difluorosulfonylamide salt (LiDFSA, Lithium difluorosulfonylamide), Lithium trifluoromethanesulfonate salt (LiTFMS, Lithium trifluoromethanesulfonate), Lithium 4,5-dicyano-2-(trifluoromethyl)imidazole salt (LiTDI, Lithium 4,5-dicyano-2-(trifluoromethyl)imidazole), Lithium nitrate salt (LiNO3, Lithium nitrate), Lithium chloride salt (LiCl, Lithium chloride), Lithium bromide salt (LiBr,Lithium bromide), Lithium iodide (LiI), Lithium pyridinium hexafluorophosphate (LiPyrF6), Lithium tetrachloroaluminate (LiAlCl4), 1-Ethyl-3-methylimidazolium TFSI + Lithium TFSI ([EMIm][TFSI] + LiTFSI), N-propyl-N-methylpyrrolidinium FSI + Lithium FSI ([PY13][FSI] + LiFSI), 1-Butyl-1-methylpyrrolidinium TFSI + Lithium FSI ([BMP][TFSI] + LiFSI, It may be 1-butyl-1-methylpyrrolidinium TFSI + Lithium FSI), lithium difluorophosphate salt (LiPO2F2, Lithium difluorophosphate).

[0037] The above medium is dimethoxyethane (C4H 10 O2, 1,2-Dimethoxyethane (DME)), diethylene glycol dimethyl ether (C6H 14 O3, Diethylene glycol dimethyl ether (DEGDME)), tetraethylene glycol dimethyl ether (C8H 18 O4, Tetraethylene glycol dimethyl ether (TEGDME)), glycol ether (C4H 10 O2, Mono- / Di- / Tri-glyme (G1 / G2 / G3)), Tetrahydrofuran (C4H8O, Tetrahydrofuran (THF)), Dioxolane (C3H6O2, 1,3-Dioxolane (DOL)), Diethoxyethane (C6H 14O2, 1,2-Diethoxyethane (dDME)), ethyl methyl carbonate (C4H8O3, Ethyl methyl carbonate (EMC)), diethyl carbonate (C5H 10 O3, Diethyl carbonate (DEC)), Dimethyl carbonate (C3H6O3, Dimethyl carbonate (DMC)), Fluoroethyl methyl carbonate (C4H7FO3, Fluoroethyl methyl carbonate (FEMC)), Fluoroethylene carbonate (C3H3FO3, Fluoroethylene carbonate (FEC)), Fluorinated dimethoxyether (C4H8F6O, Fluorinated DME (F-DME)), Tetrafluoroethyl ether (C6H4F8O, 1,1,2,2-Tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE)), Hydrofluoroether (CF3CH2OR (various), Hydrofluoroethers (HFE)), Bis-trifluoroethyl ether (C6H6F6O, Bis(2,2,2-trifluoroethyl) ether (BTFE)), Trifluoroethyl ether (C3H7FO, Trifluoroethyl ether (TFE)), sulfolane (C4H8O2S), methyl sulfone (CH4O2S), diphenyl sulfone (C 12 H 10 O2S, Diphenyl sulfone), Imedazolinium-based ionic solution ([C6H 11 N2][TFSI], 1-Ethyl-3-methylimidazolium TFSI ([EMIm][TFSI])), pyrrolidinium-based ionic solution ([C7H 16 N][FSI], N-propyl-N-methylpyrrolidinium FSI ([PY13][FSI])), butyl-methylpyrrolidinium-based ionic solution ([C9H 20It may include one or a combination of two or more of [N][TFSI], Butyl-methylpyrrolidinium TFSI ([BMP][TFSI])), Acetonitrile (CH3CN, Acetonitrile (AN)), Propylene carbonate (C4H6O3, Propylene carbonate (PC)), Trifluoropropylene carbonate (C4H3F3O3, Trifluoropropylene carbonate (TFP)), Nitromethane (CH3NO2, Nitromethane), and Methyl acetate / Ethyl acetate (CH3COOCH3 / CH3COOC2H5, Methyl acetate / Ethyl acetate). As an example, the medium may be a combination of dimethyl carbonate and fluoroethylene carbonate. In addition to the lithium salt and the medium, the liquid electrolyte may further include an additive. For example, the additive may be LiNO3.

[0038] Additionally, the above electrolyte may be formed into an electrolyte system. The electrolyte system may be formed from any one or more combinations of a fully fluorinated electrolyte (FFE), a weak solvent-based electrolyte (WSE), a high-concentration electrolyte (HCE), a localized high-concentration electrolyte (LHCE), a silicone-based electrolyte (siloxane-based), and an ionic liquid (IL).

[0039] The representative electrolyte salt constituting the above electrolyte system can be one of LiFSI (Lithium bis(fluorosulfonyl)imide) or LiTFSI (Lithium bis(trifluoromethanesulfonyl)imide).

[0040] Representative solvents for Fully Fluorinated solvents can be one of FEC (Fluoroethylene carbonate), FEMC (Fluoroethyl methyl carbonate), TFEP (Trifluoroethyl phosphate), TTE (1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether), or BTFE (Bis(trifluoroethyl) ether). Representative solvents for Weak Solvent solvents can be one of DME (Dimethoxyethane), DOL (Dioxolane), or Diglyme. Representative solvents for High-Concentration (HCE) solvents can be one of DME or an EC (Ethylene carbonate) / DEC (Diethyl carbonate) mixture. Representative solvents for Localized High-Concentration (LHCE) solvents can be one of DME or EC / DEC plus a diluent (TTE, HFE (Hydrofluoroether), etc.). Representative solvents for silicone (siloxane)-based solvents can be either polysiloxane-based solvents or MeSi(methyl siloxane). Representative solvents for ionic liquids (IL) are PYR 14 It can be one of TFSI (N-methyl-N-butyl pyrrolidinium TFSI), EMI-TFSI (1-ethyl-3-methylimidazolium TFSI), etc.

[0041] The above positive active material (30) is a nickel-cobalt-aluminum oxide containing lithium (Li(NiCoAl)O2, NCA), a nickel-cobalt-manganese oxide containing lithium (Li(NiCoMn)O2, NCM or NMC), a lithium manganese oxide (LiMn2O4, LMO), a lithium iron phosphate (LiFePO4, LFP), a lithium cobalt oxide (LiCoO2, LCO), and a manganese-iron-phosphate containing lithium (LiMn x Fe 1-x It may include at least one of Mn4PO4, LMFP.

[0042] When charging the lithium secondary battery, lithium ions are separated from the positive active material (30), and a negative electrode layer (not shown) can be formed on the negative electrode current collector (10).

[0043] For example, if the positive active material (30) is formed of a nickel-cobalt-manganese oxide containing lithium, lithium ions can be separated from the positive active material (30) through the following chemical formula 1. The separated lithium ions can be reduced on the negative current collector (10) to form a negative electrode layer.

[0044] Chemical formula 1:

[0045]

[0046] An anode plate can be formed by compressing the above-mentioned positive active material (30). That is, the anode plate can be formed by compressing the positive active material powders. The compression of the positive active material powders can be performed by a previously known method such as roll compression.

[0047] With the positive active material (30) placed on the positive current collector (20), the positive active material (30) and the positive current collector (20) can be compressed together. In this case, the positive plate can be attached to the positive current collector (20) at the same time as the positive plate is formed. Alternatively, the positive plate may be attached to the positive current collector (20) after the positive active material (30) is formed into a positive plate through compression.

[0048] Additionally, the anode plate may further include at least one of a binder material and a conductive material. For example, the anode plate may be formed by compressing the mixture in the state where at least one of the binder material and the conductive material is mixed with the anode active material (30).

[0049] For example, the binder material may include a polymer, and known materials may be used as the binder material and the conductive material.

[0050] During the initial charging of a non-anode lithium secondary battery, a naturally formed SEI film (Natural Solid Electrolyte Interphase) can be formed on the negative current collector by a reaction between the electrolyte (40) and the negative current collector (10). For example, as shown in the main reaction formula 2 below, a naturally formed SEI film can be formed on the surface of the negative current collector (e.g., copper) by a reaction between the electrolyte (40) and the negative current collector (10).

[0051] Chemical formula 2 (no side reactions):

[0052]

[0053] Since there are already many known examples of naturally occurring SEI films resulting from the reaction (i.e., chemical reaction) between the electrolyte (40) and the negative current collector (10), a detailed description thereof is omitted.

[0054] The comparative example shown in FIG. 2(b) illustrates a state in which a naturally occurring SEI film (80) is formed on a negative current collector (10). The naturally occurring SEI film may also be called NSEI, NSEI film, or NSEI thin film.

[0055] Meanwhile, the inventors of the present invention recognized that even if a naturally occurring SEI film (80) is formed on the negative current collector (10) by the reaction between the electrolyte (40) and the negative current collector (10), it is difficult to effectively suppress dendrites that occur on the negative current collector due to repeated charging and discharging of the battery.

[0056] In order to suppress the occurrence of such dendrites, an artificial SEI layer (70) may be coated on the negative electrode current collector (10) of the negative electrode lithium secondary battery according to an embodiment of the present invention. Here, artificial SEI (Artificial Solid Electrolyte Interphase) may also be referred to as ASEI.

[0057] The artificial SEI layer (70) can also be expressed as an artificial SEI coating layer, an artificial SEI film, an artificial SEI thin film, etc.

[0058] As shown in FIG. 1 (a), an artificial SEI layer (70) of metal can be pre-coated on the negative current collector (10). That is, the artificial SEI layer (70) can be pre-coated on the negative current collector (10) before the negative current collector (10) comes into contact with the electrolyte (40).

[0059] This artificial SEI layer (70) can be coated on the negative current collector (10) in advance before the negative current collector (10) comes into contact with the electrolyte (40). That is, it is preferable that the artificial SEI layer (70) be coated on the negative current collector (10) in advance before manufacturing a non-negative lithium secondary battery.

[0060] Accordingly, during the initial charging of the non-anode lithium secondary battery, the electrolyte and the artificial SEI layer (70) may come into contact and react with each other. At this time, a naturally occurring SEI film (80) may be formed on the negative current collector by the reaction between at least a portion of the artificial SEI layer (70) and the electrolyte (40).

[0061] As shown in Fig. 1(b), during the initial charging of a non-anode lithium secondary battery, at least a portion of the electrolyte (40) and the artificial SEI layer (70) may react to form a naturally occurring SEI film (80) on the negative current collector (10).

[0062] The naturally occurring SEI film shown in Fig. 1(b) can be distinguished from the naturally occurring SEI film shown in Fig. 2(b) and may have different compositions. This is because the naturally occurring SEI film shown in Fig. 1(b) is formed by the reaction of at least a portion of the electrolyte (40) and the artificial SEI layer (70), while the naturally occurring SEI film shown in Fig. 2(b) is formed by the reaction of the electrolyte (40) and the negative current collector (10).

[0063] For example, the formation of a naturally occurring SEI film through the reaction of at least a portion of the artificial SEI (70) layer and the electrolyte (40) can be represented as shown in the main reaction formulas 3 to 5 below.

[0064] Chemical formula 3 (no side reactions):

[0065]

[0066] Chemical formula 4 (no side reactions):

[0067]

[0068] Chemical formula 5 (no side reactions):

[0069]

[0070] Additionally, referring to Fig. 1(b), when the above-mentioned non-negative lithium secondary battery is first charged, the above-mentioned natural SEI film (80) can be formed on the above-mentioned negative current collector (10) by the reaction between the entire artificial SEI layer (70) and the electrolyte (40).

[0071] In contrast, when the above-mentioned non-anode lithium secondary battery is first charged, the naturally occurring SEI film (80) may be formed on the artificial SEI layer (70) that remains unreacted due to the reaction between a part of the artificial SEI layer (70) and the electrolyte (40).

[0072] In any case, the film (70, 80) on the negative current collector (10) shown in Fig. 1 (b) can also be referred to as a dual coating layer, dual film, dual layer, etc., because both the artificial SEI layer (70) pre-coated on the negative current collector (10) and the naturally occurring SEI film (80) are applied.

[0073] The inventors of the present invention were able to recognize through experiments that when an artificial SEI layer (70), which is a metal coating layer, is coated on a negative electrode current collector (10), the occurrence of dendrites can be significantly suppressed.

[0075] FIG. 3a is a microscopic image of the surface of a negative current collector coated with an artificial SEI layer, and FIG. 3b is a microscopic image of the surface of a negative current collector without an artificial SEI layer as a comparative example. Specifically, FIG. 3a is a microscopic image of the surface of a negative current collector coated with an artificial SEI layer after the battery has been charged and discharged multiple times. FIG. 3b is a microscopic image of the surface of a negative current collector without an artificial SEI layer after the battery has been charged and discharged multiple times.

[0076] As indicated by the dotted circle in Fig. 3b, it can be seen that a relatively large number of dendrites are formed on the surface of the cathode current collector without an artificial SEI layer.

[0077] In contrast, referring to Fig. 3a which shows the surface of a cathode current collector with an artificial SEI layer formed thereon, it can be seen that a smooth surface is maintained with the occurrence of dendrites suppressed.

[0078] Additionally, FIG. 4a is a microscopic image of a cross-section of a negative electrode layer on a negative current collector coated with an artificial SEI layer, and FIG. 4b is a microscopic image of a cross-section of a negative electrode layer on a negative current collector without an artificial SEI layer as a comparative example. Specifically, FIG. 3a is a microscopic image of a cross-section of a negative electrode layer on a negative current collector coated with an artificial SEI layer after the battery has been charged and discharged multiple times. Additionally, FIG. 3b is a microscopic image of a cross-section of a negative electrode layer on a negative current collector without an artificial SEI layer after the battery has been charged and discharged multiple times.

[0079] Referring to Fig. 4b, the thickness of the cross-section of the cathode layer on the cathode current collector without an artificial SEI layer is approximately 25 μm, and it can be confirmed that the cathode layer has a relatively large thickness due to the occurrence of dendrites.

[0080] In contrast, referring to Fig. 4a which shows a cross-section of the cathode layer on a cathode current collector with an artificial SEI layer formed thereon, it can be seen that the generation of dendrites is suppressed and the thickness of the cathode layer is maintained at approximately 15 μm, which is relatively small.

[0081] In this way, according to the present invention, by pre-coating an artificial SEI layer (70) on the negative electrode current collector (10), the occurrence of dendrites in the negative electrode layer can be suppressed.

[0082] Meanwhile, the inventors of the present invention conducted an experiment regarding the improvement of the lifespan of a lithium secondary battery depending on whether an artificial SEI layer (70) is coated on a negative electrode current collector (10).

[0084] Figure 5 is a diagram showing a comparison of capacity retention rates according to the number of charge and discharge cycles in the case where an artificial SEI layer is applied and in the case where it is not applied.

[0085] Specifically, FIG. 5 is a graph comparing the capacity retention rate according to the number of charge-discharge cycles in the case where only a naturally occurring SEI film formed by the reaction between the negative current collector and the electrolyte is applied on the negative current collector, and in the case where an artificial SEI layer coating and a naturally occurring SEI film formed by the reaction between the artificial SEI layer and the electrolyte are applied together on the negative current collector.

[0086] In Fig. 5, the horizontal axis represents the number of charge and discharge cycles and the vertical axis represents the capacity retention rate.

[0087] Referring to Figure 5, the electrolytes used in the experiment are localized high-concentration electrolyte (LHCE) and fluorinated electrolyte (FE).

[0088] Figure 5 shows two comparative examples in which there is no coating of an artificial SEI layer on the cathode current collector and two comparative examples in which an artificial SEI layer is pre-coated on the cathode current collector.

[0089] Specifically, in the absence of an artificial SEI layer coating on the cathode current collector, Comparative Example 1 (LHCE only) shows a naturally occurring SEI film formed on the cathode current collector by the reaction between the local high-concentration electrolyte and the cathode current collector, and Comparative Example 2 (FE only) shows a naturally occurring SEI film formed on the cathode current collector by the reaction between the fluorinated electrolyte and the cathode current collector.

[0090] In addition, with an artificial SEI layer already coated on the cathode current collector, Comparative Example 3 (LHCE+ASEI) shows that a naturally occurring SEI film is additionally formed on the cathode current collector by the reaction between the local high-concentration electrolyte and the artificial SEI layer, and Comparative Example 4 (FE+ASEI) shows that a naturally occurring SEI film is additionally formed on the cathode current collector by the reaction between the fluorinated electrolyte and the artificial SEI layer.

[0091] As shown in FIG. 5, compared to Comparative Examples 1 and 2 (LHCE only, FE only) in which an artificial SEI layer is not pre-coated on the cathode current collector, it can be seen that the decrease in capacity retention rate according to the number of charge-discharge cycles is relatively small in Comparative Examples 3 and 4 (LHCE+ASEI, FE+ASEI) in which an artificial SEI layer is pre-coated on the cathode current collector.

[0092] That is, when the same number of charge and discharge cycles are repeated, Comparative Examples 3 and 4 (LHCE+ASEI, FE+ASEI), in which an artificial SEI layer is pre-coated on the cathode current collector, exhibit a larger capacity retention rate compared to Comparative Examples 1 and 2 (LHCE only, FE only), in which an artificial SEI layer is not pre-coated on the cathode current collector.

[0093] In other words, when comparing the number of charge-discharge cycles to reach a specific capacity retention rate (e.g., 80% capacity retention rate), compared to Comparative Examples 1 and 2 (LHCE only, FE only) in which an artificial SEI layer is pre-coated on the cathode current collector, more charge-discharge cycles can be secured in Comparative Examples 3 and 4 (LHCE+ASEI, FE+ASEI) in which an artificial SEI layer is pre-coated on the cathode current collector.

[0094] In this way, when an artificial SEI layer is pre-coated on the negative current collector, the capacity and lifespan of the battery can be relatively increased.

[0095] Meanwhile, the inventors of the present invention were able to confirm through experiments that it is preferable for the artificial SEI layer (70) to include a mixture of metals selected from the group of transition metals. For example, the artificial SEI layer (70) may include a mixture of two metals selected from the group of transition metals in the form of a system.

[0096] For example, the artificial SEI layer may be formed from an Ag-Ti system. Here, the Ag-Ti system does not refer to an alloy of Ag and Ti, but rather to a state in which Ag and Ti are laminated (i.e., coated) on a cathode current collector.

[0097] In the Ag-Ti system, the stacking order of Ag and Ti on the negative current collector can be arbitrary. For example, Ag may be stacked first on the negative current collector, followed by Ti on top of it. Conversely, Ti may be stacked first on the negative current collector, followed by Ag on top of it.

[0098] In addition, Ag and Ti can be repeatedly and alternately stacked on the negative current collector. That is, Ag and Ti can be stacked on the negative current collector in multiple layers.

[0099] The above Ag-Ti system can also be expressed as an Ag-Ti layer, an Ag-Ti coating layer, an Ag-Ti film, an Ag-Ti thin film, etc.

[0100] Ag-Ti-based coatings for forming an artificial SEI layer on a cathode current collector can be performed through known methods such as roll coating, spray coating, slot die coating, blade coating, dry coating, and vacuum coating.

[0101] According to the present invention, by coating an artificial SEI layer (70) formed of an Ag-Ti system onto a negative electrode current collector (10), the occurrence of dendrites in the negative electrode layer (60) during battery charging can be suppressed.

[0102] Meanwhile, although an embodiment in which the artificial SEI layer is formed from an Ag-Ti system has been described, the artificial SEI layer may also be formed from a system containing indium (In) or magnesium (Mg).

[0103] The Ag-Ti system will be explained in more detail below with reference to other drawings.

[0105] FIG. 6 is a diagram showing a comparison of capacity retention rates according to the number of charge-discharge cycles. Specifically, FIG. 6 shows the change in capacity retention rate (vertical axis) according to the number of charge-discharge cycles (horizontal axis) in an Ag-Ti system forming an artificial SEI layer (70).

[0106] In FIG. 6, the dotted line represents a reference in which no artificial SEI layer is provided on the cathode current collector, the single-dotted line represents an example in which Ag:Ti is included in a ratio of 4:1 based on the total volume of the Ag-Ti system in the artificial SEI layer Ag-Ti system, the two-dotted line represents an example in which Ag:Ti is included in a ratio of 16:1 based on the total volume of the Ag-Ti system in the artificial SEI layer Ag-Ti system, and the solid line represents an example in which Ag:Ti is included in a ratio of 10:1 based on the total volume of the Ag-Ti system in the artificial SEI layer Ag-Ti system.

[0107] Referring to Figure 6, it can be seen that compared to a reference without an artificial SEI layer formed of an Ag-Ti system, the decrease in capacity retention rate according to the number of charge-discharge cycles is relatively small when an artificial SEI layer formed of an Ag-Ti system is included.

[0108] In other words, when the same number of charge and discharge cycles are repeated, the case including an artificial SEI layer formed of Ag-Ti exhibits a higher capacity retention rate compared to the reference that does not include an artificial SEI layer formed of Ag-Ti.

[0109] In other words, when comparing the number of charge / discharge cycles to reach a specific capacity retention rate (e.g., 80% capacity retention rate), more charge / discharge cycles can be secured when an artificial SEI layer formed of Ag-Ti is included compared to a reference that does not include an artificial SEI layer formed of Ag-Ti.

[0110] In this way, when including an artificial SEI layer formed from an Ag-Ti system, the capacity and lifespan of the battery can be relatively increased.

[0111] Meanwhile, the inventors of the present invention conducted an experiment to compare the case including an artificial SEI layer formed of an Ag-Ti system and the case not including it, in relation to the relationship between the battery State of Health (SOH) and the number of charge and discharge cycles.

[0112] Figure 7 is a diagram showing a comparison of the number of charge and discharge cycles of a battery until the battery health status reaches 80% (i.e., up to SOH 80%).

[0113] Generally, the replacement time for electric vehicle (EV) batteries is considered when the State of Health (SOH) reaches 70–80%. In other words, an SOH of 80% means that the battery is aging normally and is still usable, but it implies a state where driving range and charging speed may decrease compared to the initial state.

[0114] Referring to Fig. 7, it can be seen that compared to a reference without an artificial SEI layer formed of an Ag-Ti system, the number of charge-discharge cycles up to SOH 80% is greater when an artificial SEI layer formed of an Ag-Ti system is included.

[0115] In other words, when comparing the number of charge and discharge cycles to reach a specific battery health state (e.g., SOH 80%), more charge and discharge cycles can be secured when an artificial SEI layer formed of Ag-Ti is included compared to a reference that does not include an artificial SEI layer formed of Ag-Ti.

[0116] In this way, when including an artificial SEI layer formed from an Ag-Ti system, the capacity and lifespan of the battery can be relatively increased.

[0117] Meanwhile, as in the example, since Ag and Ti are stacked alternately in a laminate form on the negative current collector in one layer or multiple layers, the volume of Ag and Ti can be determined based on the thickness of the Ag and Ti stacked on the negative current collector.

[0118] The inventors of the present invention conducted an experiment to compare the change in capacity retention rate according to the number of charge-discharge cycles based on the volume of Ag and the volume of Ti in an Ag-Ti system forming an artificial SEI layer (70).

[0119] Referring to FIGS. 6 and 7, the Ag-Ti system of the artificial SEI layer may contain 5 to 25% of the volume of Ti based on the total volume of the Ag-Ti system. In other words, the artificial SEI layer may contain 5 to 25% of the volume of Ti based on the total volume of the artificial SEI layer.

[0120] Preferably, the Ag-Ti system of the artificial SEI layer may contain about 9% of the volume of Ti based on the total volume of the Ag-Ti system. In other words, the artificial SEI layer may contain about 9% of the volume of Ti based on the total volume of the artificial SEI layer.

[0121] In addition, the Ag-Ti system of the artificial SEI layer may contain Ag:Ti in a ratio of 4:1 to 16:1 based on the total volume of the Ag-Ti system. In other words, the artificial SEI layer may contain Ag:Ti in a ratio of 4:1 to 16:1 based on the total volume of the artificial SEI layer.

[0122] Preferably, the Ag-Ti system of the artificial SEI layer may contain Ag:Ti in a ratio of 10:1 based on the total volume of the Ag-Ti system. In other words, the artificial SEI layer may contain Ag:Ti in a ratio of 10:1 based on the total volume of the artificial SEI layer.

[0123] In this way, when an artificial SEI layer formed of an Ag-Ti system in a specific ratio is coated on the negative electrode current collector of a lithium secondary battery, the occurrence of dendrites is suppressed, and the capacity and lifespan of the lithium secondary battery can be increased.

[0124] Meanwhile, the inventors of the present invention were able to obtain characteristic peak values ​​by testing the cathode current collector coated with the artificial SEI layer using copper K-alpha rays. Furthermore, the inventors confirmed that the composition of the Ag-Ti system of the artificial SEI layer could be determined based on these characteristic peak values.

[0126] Figure 8 is a diagram showing the results of testing a cathode current collector coated with an artificial SEI layer by copper K-alpha line.

[0127] Referring to FIG. 8, when a negative current collector coated with an artificial SEI layer included in a lithium secondary battery according to the present invention was tested by a copper K-alpha line (k = 1.5406 Å), one or more characteristic peak values ​​were obtained.

[0128] Specifically, the inventors found that, as a result of testing copper K-alpha lines on an artificial SEI layer formed of an Ag-Ti system, characteristic peaks appeared at at least one of 2θ=38°, 2θ=44°, 2θ=64° and 2θ=77° in the X-ray diffraction pattern.

[0129] In a lithium secondary battery according to an embodiment of the present invention, the Ag-Ti system can be formed such that when the negative current collector coated with the artificial SEI layer is tested by copper K-alpha rays, a characteristic peak appears at at least one of 2θ=38°, 2θ=44°, 2θ=64°, and 2θ=77° of the X-ray diffraction pattern. That is, in a lithium secondary battery according to an embodiment of the present invention, the characteristics of the Ag-Ti system (e.g., at least one of the volume ratio of Ag and Ti, stacking thickness, and number of stacking layers) can be determined such that a characteristic peak appears at at least one of 2θ=38°, 2θ=44°, 2θ=64°, and 2θ=77° of the X-ray diffraction pattern.

[0130] More specifically, the inventors found that, as a result of testing copper K-alpha lines on an artificial SEI layer formed of a specific ratio of Ag-Ti system (e.g., Ag:Ti = 10:1), characteristic peaks appeared at 2θ=38°, 2θ=44°, 2θ=64°, and 2θ=77° of the X-ray diffraction pattern.

[0131] Preferably, in a lithium secondary battery according to an embodiment of the present invention, the Ag-Ti system may be formed such that when the negative current collector coated with the artificial SEI layer is tested by copper K-alpha line, characteristic peaks appear at all of 2θ=38°, 2θ=44°, 2θ=64°, and 2θ=77° of the X-ray diffraction pattern. That is, in a lithium secondary battery according to an embodiment of the present invention, the characteristics of the Ag-Ti system (e.g., at least one of the volume ratio of Ag and Ti, stacking thickness, and number of stacking layers) may be determined such that characteristic peaks appear at all of 2θ=38°, 2θ=44°, 2θ=64°, and 2θ=77° of the X-ray diffraction pattern.

[0132] The above-mentioned angle of 2θ is an approximate value in the test result graph, and the more accurate angle of 2θ at which the characteristic peak appears can be 2θ=38.2°, 2θ=44.3°, 2θ=64.5°, and 2θ=77.5°.

[0133] In this way, according to the present invention, by testing a negative current collector coated with an artificial SEI layer by copper K-alpha line, the characteristics of the Ag-Ti system forming the artificial SEI layer (e.g., at least one of the volume ratio of Ag and Ti, stacking thickness, and number of stacking layers) can be determined.

[0135] The preferred embodiments of the present invention described above are disclosed for illustrative purposes only, and those skilled in the art with ordinary knowledge of the present invention will be able to make various modifications, changes, and additions within the spirit and scope of the present invention, and such modifications, changes, and additions should be considered to fall within the scope of the following claims. Explanation of the symbols

[0136] 10 cathode current collector 20 all-positive collectors 30 positive electrode active material 40 electrolytes 50 Separator 70 Artificial SEI layer 80 Naturally occurring SEI membrane

Claims

Claim 1 A non-anode lithium secondary battery having a negative electrode current collector having a dual coating layer formed thereon, wherein a positive active material, a separator, and an electrolyte are provided between a positive electrode current collector and a negative electrode current collector, wherein an artificial SEI (Solid Electrolyte Interphase) layer of metal is coated on the negative electrode current collector, and during the initial charging of the non-anode lithium secondary battery, a naturally occurring SEI film is formed on the negative electrode current collector by a reaction between at least a portion of the artificial SEI layer and the electrolyte, and wherein the artificial SEI layer is formed of an Ag-Ti system. Claim 2 A non-anode lithium secondary battery having a negative electrode current collector having a dual coating layer, characterized in that, in the first charging of the non-anode lithium secondary battery, the naturally occurring SEI film is formed on the negative electrode current collector by the reaction of at least a portion of the artificial SEI layer and the electrolyte. Claim 3 A non-cathode lithium secondary battery according to claim 1 or 2, characterized in that the artificial SEI layer is not an alloy of Ag and Ti, but rather Ag and Ti are coated on a negative current collector in a laminate form. Claim 4 A non-cathode lithium secondary battery according to claim 3, wherein the artificial SEI layer is formed by alternately and repeatedly coating Ag and Ti on the negative current collector. Claim 5 A non-anode lithium secondary battery according to claim 4, characterized in that the Ag-Ti system of the artificial SEI layer contains Ag:Ti in a volume ratio of 4:1 to 16:1 based on the total volume of the Ag-Ti system. Claim 6 A negative lithium secondary battery according to claim 1, characterized in that the Ag-Ti system is formed such that when the negative current collector coated with the artificial SEI layer is tested by copper K-alpha rays, a characteristic peak appears at at least one of 2θ°, 2θ°, 2θ° and 2θ° of the X-ray diffraction pattern. Claim 7 A non-cathode lithium secondary battery according to claim 6, characterized in that the Ag-Ti system is formed such that when the negative current collector coated with the artificial SEI layer is tested by copper K-alpha rays, characteristic peaks appear at all of 2θ°, 2θ°, 2θ° and 2θ° of the X-ray diffraction pattern.